Research on Talent Policy and Optimization Path of Wuhan City based on SWOT Analysis - Zhang, Shiqi; Li, Jiyun; Zhao, Ziyi (International Journal of Social Sciences and Public Administration, 2024)
This study adopts SWOT analysis to analyze Wuhan’s talent policy in depth, aiming to explore its advantages, disadvantages, opportunities and challenges. The study finds that Wuhan has significant geographical location and resource advantages in terms of talent policy, as well as outstanding performance in policy innovation and talent cultivation. However, there are also problems such as talent drain and insufficient policy implementation. In the face of fierce competition for talents at home and abroad, Wuhan should seize the opportunity to strengthen policy promotion and implementation, optimize the talent service system, and enhance the attractiveness of talents. This study proposes targeted optimization paths, including improving the talent policy system, strengthening the construction of talent teams, and improving the quality of talent services, with a view to promoting the sustainable development and optimization of Wuhan’s talent policy.